Country Culture and National Innovation - Khan, Raihan; Cox, Pamela (Archives of Business Research, 2017)
Innovation, the implementation of creative ideas, is not only vital to growth but also to survival as companies and nations must innovate to compete in a rapidly changing global economy. Researchers are just beginning to understand the relationship between country culture and innovation. In a number of studies, cultural dimensions have correlated significantly with measures of innovation and creativity. However, it is difficult to compare findings across studies as multiple frameworks have been used to operationalize culture. Likewise, measures of innovation vary widely across studies. This paper proposes using a new index, the Global Innovation Index (GII), and Hofstede’s cultural dimensions to explore the relationships between country culture and innovation. We begin with definitions and a discussion of innovation and national culture. Then, measures of national culture, innovation, and creativity are critically discussed, and followed by a review of existing research on country culture and innovation. Hypotheses are proposed and tested using Hofstede’s dimensions and the Global Innovation Index. Our results indicate support for four out of the six hypotheses and suggest that innovative societies are characterized by the following cultural values: individualism, low masculinity, pragmatism, and indulgence.